We have this:
20y^2 - 5x^2
To solve, we factor to simplify.
Factor out 5. Why? We factor out 5 because it is the BIGGEST number that evenly (without a remainder) can be divided by itself and 20. See it? I will divide 20 by 5 and then 5 by 5.
20y^2 - 5x^2 becomes 5(4y^2 - x^2).
Do you see the terms inside the parentheses?
We need to break this down a bit more.
The inside terms must be factored as well.
4y^2 - x^2 becomes (2y - x) (2y + x)
Final answer: 5 (2y-x) (2y+x)
Notice that our final answer is 3 factors. See it?
Guido
2006-10-25 14:51:37
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
20y^2- 5x^2=5(4y^2-x^2) you didn't say, but I'm guessing that you want this to equal zero. If so
5(4y^2-x^2)=0
4y^2-x^2=0
4y^2=x^2
x=+/-2y
2006-10-25 14:46:04
·
answer #2
·
answered by yupchagee 7
·
0⤊
0⤋
20y^2 - 5x^2 = 5(4y^2 - x^2) = 5(2y - x)(2y + x)
2006-10-25 15:45:48
·
answer #3
·
answered by Sherman81 6
·
0⤊
0⤋
15y2x2 the twos are raised up like u said
2006-10-25 14:48:58
·
answer #4
·
answered by LIL SERIA 2
·
0⤊
0⤋
well... you didn't set it equal to anything, but you can factor it as follows:
5(4y^2-x^2)
5(2y+x)(2y-X)
2006-10-25 14:46:21
·
answer #5
·
answered by Yoni 2
·
0⤊
0⤋
if u working ; on organic numbers or reals (the place u have finished variety gadget available) then that's 10; yet while u are engaged on limited contraptions like Z10; Z9... then that's diverse. So please specify the place are u working (wherein set)
2016-12-08 21:27:09
·
answer #6
·
answered by ? 4
·
0⤊
0⤋
5 (4y^2 - x^2)
= 5(2y + x)(2y - x)
2006-10-25 14:46:16
·
answer #7
·
answered by Up_In_Smoke 2
·
0⤊
0⤋
assume that x=2
20y^2-5(2)^2=0
20y^2=5(2)^2
20y^2=20
y^2=20/20
y^2=1
y=1
20(1)^2=5(x)^2
20=5(x)^2
20/5=x^2
4=x^2
x=2
checking:
20y^2=5(x)^2
20(1)^2=5(2)^2
20(1)=5(4)
20=20
2006-10-25 15:06:58
·
answer #8
·
answered by ladjot 1
·
0⤊
0⤋
40y-10
2006-10-25 15:53:20
·
answer #9
·
answered by yahoo sucks 3
·
0⤊
0⤋